IMPLEMENTASI SISTEM MANAJEMEN PEMBELAJARAN (LEARNING MANAGEMENT SYSTEM) DALAM PENGEMBANGAN PROFESIONAL BERKELANJUTAN (CONTINOUS PROFESSIONAL DEVELOPMENT) GURU SMK (STUDI KASUS DI SMK N KOTA BANDUNG) - Setia Aji, - (2022)
The development of Internet technology has given rise to various new applications, including applications for the education sector, that is, the learning management system (LMS). The purpose of this study was to determine the implementation of LMS in schools in the continuous professional development of vocational high school teachers. Data was collected through questionnaires using google forms on WhatsApp, semi-structured interviews, and documentation study. The research method uses a quantitative descriptive approach with an analysis of the Structural Equation Modelling (SEM) approach based on the Smart Partial Least Square (Smart PLS) software. The sample in this study were 75 productive teachers in the field of electrical engineering expertise and electronics engineering expertise at four state vocational high schools (SMKN) in Bandung. The results showed that school support has a positive and significant effect on self-development. The results of data analysis showed that the value of the influence of the school support variable on self-development was 0.2 with a p-value of 0.048 (<0.05). Meanwhile, technical support has a positive and insignificant effect on self-development. This is indicated by the value of the influence of the technical support variable on self-development of 0.21 with a p-value of 0.123 (>0.05). Meanwhile, self-efficacy has a positive and significant effect on teacher self-development. And the value of the influence of the self-efficacy variable on self-development is 0.484 with a p-value of 0.000 (<0.05). It was found that the problems occurred in the implementation of the LMS in schools were divided into 3 factors, firstly, the teacher factor consisting of teacher motivation, readiness, responsibility, and teacher-owned equipment; secondly, school support factors covering school policies, costs of procurement and maintenance of school LMS, Internet facilities, and school computer facilities; and thirdly, technical support factors including the ease of use of the school LMS, the features available in the school LMS, and the development and progress of ICT in the school LMS.